2022
DOI: 10.1096/fj.202201418r
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the transcriptional response to resistance exercise over 4 weeks of daily training

Abstract: We present the time course of change in the muscle transcriptome 1 h after the last exercise bout of a daily resistance training program lasting 2, 10, 20, or 30 days. Daily exercise in rat tibialis anterior muscles (5 sets of 10 repetitions over 20 min) induced progressive muscle growth that approached a new stable state after 30 days. The acute transcriptional response changed along with progressive adaptation of the muscle phenotype. For example, expression of type 2B myosin was silenced. Time courses recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 72 publications
(161 reference statements)
5
28
0
Order By: Relevance
“…We recently reported that Myc induction specifically in muscle fibres is central to the acute mechanical loading‐induced transcriptome in the plantaris of young mice (Murach et al., 2022). A corroborating result in muscle tissue was reported with frequent resistance‐type training in rats (Viggars et al., 2022). Furthermore, the induction of Myc was recently linked to ‘biological immortality’ in hydrozoans (Pascual‐Torner et al., 2022).…”
Section: Introductionsupporting
confidence: 83%
“…We recently reported that Myc induction specifically in muscle fibres is central to the acute mechanical loading‐induced transcriptome in the plantaris of young mice (Murach et al., 2022). A corroborating result in muscle tissue was reported with frequent resistance‐type training in rats (Viggars et al., 2022). Furthermore, the induction of Myc was recently linked to ‘biological immortality’ in hydrozoans (Pascual‐Torner et al., 2022).…”
Section: Introductionsupporting
confidence: 83%
“…Muscle adaptations are thought to stem from the molecular response to each exercise session (Perry et al ., 2010; Viggars et al ., 2023), which when repeated over time leads to phenotypical differences (Chapman et al ., 2020). Our results show that a single extensive resistance exercise session in strength athletes, leads to mild changes in mitochondrial morphological variables, in the SS and to a lower extent in the SMF, associated with mitochondrial stress (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypical adaptations following months or years of training stem from the accumulative effect of repeated exercise over time (Perry et al ., 2010; Viggars et al ., 2023). The acute molecular cascade initiated following an acute resistance exercise bout involves the upregulation of a large number of genes including ribosomal and myogenic pathways that will support the increased synthesis of myofibrillar proteins (Bamman et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypical adaptations following months or years of training stem from the cumulative effect of repeated exercise over time (Perry et al., 2010; Viggars et al., 2023). The acute molecular cascade initiated following an acute resistance exercise bout involves the upregulation of a large number of genes including ribosomal and myogenic pathways that will support the increased synthesis of myofibrillar proteins (Bamman et al., 2018).…”
Section: Introductionmentioning
confidence: 99%